Festival Romanistica. Contribuciones lingüísticas - Contributions linguistiques - Contributi linguistici - Contribuições linguísticas - Engwall, Gunnel; Fant, Lars (Stockholm Studies in Romance Languages, 2015)
Festival Romanisticais an edited volume with 19 contributions written in four Romance languages: French, Italian, Portuguese and Spanish. The volume represents the whole range of research areas in Romance Linguistics today at the University of Stockholm: semantics, syntax, pragmatics, discourse analysis, diachronic linguistics, translation studies and second language acquisition and use. Five of the articles are written by renowned scholars from five European universities. The authors of the remaining 14 contributions are doctors and supervisors belonging to the National Doctoral Program in Romance Languages (FoRom). By virtue of its wide scope and the high quality of its contributions, this volume is of interest for, and will find a natural audience among, researchers of all Romance Languages departments and divisions in Scandinavia, Europe and worldwide.Festival Romanisticais the first volume in Stockholm Studies in Romance Languages, which is a peer-reviewed series of monographs and edited volumes.Editors:Gunnel Engwall is Professor of Romance Languages, especially French, at Stockholm University. She has been Vice-Chancellor of Stockholm University and President of the Academy of Letters, Antiquity and History and is presently the Head of the National Edition of August Strindberg's Collected Works. Lars Fant is Professor emeritus of Romance Languages, especially Spanish and Portuguese, at Stockholm University. He is the also Chief Editor of the series Stockholm Studies in Romance Languages.